2010
DOI: 10.1016/j.joep.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

When equality trumps reciprocity

Abstract: Inequity aversion and reciprocity have been identified as two primary motivations underlying human decision making. However, because income and wealth inequality exist to some degree in all societies, these two key motivations can point to different decisions. In particular, when a beneficiary is less wealthy than a benefactor, a reciprocal action can lead to greater inequality. In this paper we report data from a trust game variant where trustees' responses to kind intentions generate inequality in favor of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 43 publications
(8 reference statements)
13
60
0
Order By: Relevance
“…MAST could similarly explain the finding that disadvantaged individuals tend to behave somewhat more selfishly (Xiao and Bicchieri 2010;Zitek et al 2010) and punitively (Raihani, and McAuliffe 2012): if one is perceived as being unjustly victimized-and thus come to be viewed as a better potential target of social investment-he might also be more capable of avoiding the condemnation for selfish behaviors, at least temporarily (Gray and Wegner 2011). This is due to the fact that condemning an individual is unlikely to help build an alliance with him, as condemnation signals a negative WTR.…”
Section: Why Moral Judgments Are Often Harm-centricmentioning
confidence: 99%
“…MAST could similarly explain the finding that disadvantaged individuals tend to behave somewhat more selfishly (Xiao and Bicchieri 2010;Zitek et al 2010) and punitively (Raihani, and McAuliffe 2012): if one is perceived as being unjustly victimized-and thus come to be viewed as a better potential target of social investment-he might also be more capable of avoiding the condemnation for selfish behaviors, at least temporarily (Gray and Wegner 2011). This is due to the fact that condemning an individual is unlikely to help build an alliance with him, as condemnation signals a negative WTR.…”
Section: Why Moral Judgments Are Often Harm-centricmentioning
confidence: 99%
“…Although far from universal, egalitarian beliefs and values are widely held. Political scientists and economists have found that behavior in various laboratory games, such as the prisoners' dilemma game, public goods games and the trust game, often reveals a preference for more egalitarian or equal outcomes over less egalitarian but more self-enhancing outcomes among a substantial number of players (Dawes, Fowler, Johnson, McElreath, & Smirnov, 2007;Xiao & Bicchieri, 2010). Furthermore, psychologists and sociologist have found that individual and national differences in general egalitarian beliefs predict a variety of social attitudes and behaviors (Pratto, Sidanius, Stallworth, & Malle, 1994;Schwartz, 2006).…”
Section: Treat Others As Equalsmentioning
confidence: 99%
“…For a player who does not care much about a norm, the expectation of negative sanctions will be necessary to induce conformity and if transgressions are difficult to detect, some people will be tempted to evade a norm. In ambiguous situations in which more than one norm may apply, or different 'interpretations' of a norm may be available, selfserving biases may induce individuals to discount a norm in favor of another that they prefer (Xiao and Bicchieri 2010) To test the hypothesis that norm manipulation and norm evasion are two very different phenomena, we focused on a version of the Ultimatum Game (Guth, Schmittberger, & Schwarze, 1982) in which Proposers proposed a division of a sum of $10.00 to Responders, who accepted or rejected the offer. In the case of a rejection, both parties got nothing.…”
Section: Introductionmentioning
confidence: 99%